2020
DOI: 10.21037/jtd-20-1623
|View full text |Cite
|
Sign up to set email alerts
|

Baseline impedance via manometry and ambulatory reflux testing are not equivalent when utilized in the evaluation of potential extra-esophageal gastroesophageal reflux disease

Abstract: Background: Esophageal baseline impedance (BI) shows promise for the diagnosis of gastroesophageal reflux disease (GERD), but means of acquisition and relevance to extra-esophageal manifestations of GERD (EE-GERD) remain unclear. In this study we aim to (I) evaluate concordance between BI as measured by 24-hour pH-impedance (pH-MII) and high-resolution impedance manometry (HRIM), and (II) assess relationship to potential EE-GERD symptoms. Methods: In this prospective open cohort study, patients presenting for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Another additional component of impedance testing that can potentially improve diagnostic yield is MNBI. Studies have shown poor correlation between extraesophageal symptoms and MNBI, both in the distal and proximal esophagus (23). Other studies have demonstrated that distal, but not proximal, esophageal MNBI can predict pathologic reflux in patients with isolated laryngeal reflux symptoms (24).…”
Section: Discussionmentioning
confidence: 99%
“…Another additional component of impedance testing that can potentially improve diagnostic yield is MNBI. Studies have shown poor correlation between extraesophageal symptoms and MNBI, both in the distal and proximal esophagus (23). Other studies have demonstrated that distal, but not proximal, esophageal MNBI can predict pathologic reflux in patients with isolated laryngeal reflux symptoms (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, some other studies noted that MNBI was not sufficient to evaluate patients with EES. 41 , 42 Doo et al 41 showed that there was no significant difference in the MNBI values of distal and proximal esophageal (Z6 and Z3, respectively) between patients with LPR and healthy controls. In addition, Zikos et al 42 found that there was no correlation between distal/proximal MNBI and EES.…”
Section: The Use Of Mnbi In Diagnosing Patients With Atypical Symptom...mentioning
confidence: 99%
“… 41 , 42 Doo et al 41 showed that there was no significant difference in the MNBI values of distal and proximal esophageal (Z6 and Z3, respectively) between patients with LPR and healthy controls. In addition, Zikos et al 42 found that there was no correlation between distal/proximal MNBI and EES. Whether MNBI can improve the diagnostic rate of GERD patients or predict the response to anti-reflux therapy in patients with EES or atypical symptoms is an open question to be explored in future studies.…”
Section: The Use Of Mnbi In Diagnosing Patients With Atypical Symptom...mentioning
confidence: 99%
See 1 more Smart Citation